3D electronic and photonic structures as active biological interfaces. Issue 3 (6th December 2019) - Wang, Huachun; Sun, Pengcheng; Yin, Lan; Sheng, Xing
Abstract: Biocompatible materials and structures with three‐dimensional (3D) architectures establish an ideal platform for the integration of living cells and tissues, serving as desirable interfaces between biotic and abiotic systems. While conventional 3D bioscaffolds provide a mechanical support for biomatters, emerging developments of micro‐, nano‐, and mesoscale electronic and photonic devices offer new paradigms in analyzing and interrogating biosystems. In this review, we summarize recent advances in the development of 3D functional biointerfaces, with a particular focus on electrically and optically active materials, devices, and structures. We first give an overview of representative methods for manufacturing 3D biointegrated structures, such as chemical synthesis, microfabrication, mechanical assembly, and 3D printing. Subsequently, exemplary 3D nano‐, micro‐, and mesostructures based on various materials, including semiconductors, metals, and polymers are presented. Finally, we highlight the latest progress on versatile applications of such active 3D structures in the biomedical field, like cell culturing, biosignal sensing/modulation, and tissue regeneration. We believe future 3D micro‐, nano‐, and mesostructures that incorporate electrical and/or optical functionalities will not only profoundly advance the fundamental studies in biological sciences, but also create enormous opportunities for medical diagnostics and therapies. Abstract : This review paper provides an overview about recent progress of advanced three‐dimensional (3D) electronic and photonic structures as functional platforms for active biological interfaces. Materials selections and fabrication strategies are summarized and compared, and their utilities for biomedical applications are highlighted.